Karakteristik Morfologi dan Fisiologi Isolat Pantoea stewartii subsp. stewartii pada Jagung - Yulfi Desi; Trimurti Habazar; Agustian Agustian; Ujang Khairul; Syamsuwirman Syamsuwirman; Prima Novia (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2014)
Pantoea stewartii subsp. stewartii is the pathogen causing stewart’s wilt disease in maize. The occurrence of the disease was recently reported in Indonesia with limited information. Research was conducted to characterize several isolates of P. stewartii subsp. stewartii isolated from maize plants collected from 6 districts in West Sumatra. Leaves showing yellow stripes symptoms along the vein was ground and suspeneded then the bacteria was isolated and incubated for 3 × 24 h at room temperature in nutrient glucose agar (NGA). Pure bacterial colonies gained from this medium was used for characterization. Assessment of bacterial characters was conducted based on morphological assay, physiological assay, biological assay (hypersensitivity, and pathogenicity) followed by polymerase chain reaction (PCR)-based identification. Unique characters of the family Enterobacteriaceae was observed on 7 isolates based on morphological and physiological characters, and only 4 isolates (PR1, PP, ST1, LA) gave positive reaction on hypersensitivity and pathogenicity test. Further molecular identification confirmed 3 out of 7 isolates had high homology to Pantoea stewartii, i.e. Pantoea stewartii strain R1-104, R1-132, and ATCC 29923 for isolates LA, PR1, and PR2, respectively.